The responsibility of the members of the board of directors of the association for contribution arrears - Robert Musiałkiewicz (Prawo Budżetowe Państwa i Samorządu)
Members of the associations governing bodies are responsible for their contribution arrears. Terms and conditions for this liability has been settled, as in the case of capital companies. The problem arises in the case of associations not engaged in economic activities because they do not have the ability of the receiver and systemic sclerosis, which means no request for bankruptcy and consequently impeded the possibility of liberation by the members of the board of directors from liability for contribution arrears of the association.